Information System Management for Student Discipline Based on the Attitude Record Application in an Elementary School - Badrudin, Badrudin; Muhyi, Ujang Abdul (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
This study examined the evolution of Management Information Systems (MIS) within the context of industry 4.0 era, specifically emphasizing student discipline management. The research aimed to implement the "Attitude Record" application at the Islamic Elementary School (SDI) Al Amanah in Bandung Regency, serving as a foundational database for student discipline management. The research methodology employed in this study was the school-based action research method. The research outcomes affirmed that the application of management through the "Attitude Record" application within the framework of the student discipline information system at SDI Al Amanah enabled administrators to select actions under students’ conditions. The procedural steps taken in this school-based action research had yielded substantive alterations in the arrangement and monitoring of student conduct while yielding significant effects on the educational ambience within the institution. In a comprehensive context, the discipline management founded upon the information furnished by the "Attitude Record" application had substantial contribution by enhancing oversight, reporting, and handling student disciplinary infractions. This approach extended beyond mere reliance on students' attendance criteria or advancements in specific subjects. Instead, it encompassed a comprehensive view of student behavior, enabling administrators to adopt an informed and sensitive approach to individual student contexts. Discipline management based on information provided by the "Attitude Record" application had significantly contributed to enhancing supervision, reporting, and addressing student disciplinary violations. This approach avoided limiting itself to student attendance or specific subject areas improvements. Instead, it offered a more holistic perspective on student behavior, enriching the disciplinary framework